Nuclear DNA Amounts in Chinese Bryophytes Estimated by Flow Cytometry: Variation Patterns and Biological Significances - Dandan Li; Guangyu Luo; Shuiliang Guo; Ruoling Huang; Jun Yang; Tong Cao; Jing Yu (Plants, 2023)
There exists an obvious gap in our knowledge of the nuclear DNA amount of bryophytes, not only in terms of the low number of species represented, but also in systematic and geographic representation. In order to increase our knowledge of nuclear DNA amounts and variation patterns in bryophytes, and their potential phylogenetic significances and influences on phenotypes, we used flow cytometry to determine the DNA 1C values of 209 bryophyte accessions, which belong to 145 mosses and 18 liverworts collected from China, by using Physcomitrella patens as a standard. We quantified the differences in DNA 1C values among different orders and families and constructed a phylogenetic tree of 112 mosses with four gene sequences (nad5, rbcL, trnL-F, and 18S-ITS1-5.8S-ITS2-26S). DNA 1C values were mapped onto the phylogenetic tree to test a potential phylogenetic signal. We also evaluated the correlations of the DNA 1C value with the sizes of individuals, leaves, cells, and spores by using a phylogenetically controlled analysis. New estimates of nuclear DNA amounts were reported for 145 species. The DNA 1C values of 209 bryophyte accessions ranged from 0.422 pg to 0.860 pg, with an average value of 0.561 pg, and a 2.04-fold variation covered the extremes of all the accessions. Although the values are not significantly different (p = 0.355) between mosses (0.528 pg) and liverworts (0.542 pg), there are variations to varying extents between some families and orders. The DNA 1C value size exerts a positive effect on the sizes of plants, leaves, and cells, but a negative effect on spore size. A weak phylogenetic signal is detected across most moss species. Phylogenetic signals are comparatively strong for some lineages. Our findings show that bryophytes have very small and highly constrained nuclear DNA amounts. There are nucleotype effects of nuclear DNA amounts for bryophytes at the individual, organ, and cell levels. We speculate that smaller nuclear DNA amounts are advantageous for bryophytes in dry environments. Significant differences in the DNA 1C values among some moss families and orders, as well as phylogenetic signals for some lineages, imply that nuclear DNA amount evolution in mosses seems to be unidirectional.